PEMANFAATAN SEMPADAN TUKAD BINDU SEBAGAI RUANG KREATIVITAS GENERASI MUDA DI KOTA DENPASAR - Kadek Ari Darmawan; Komang Wirawan; I Gusti Putu Anindya Putra (UNHI PRESS, 2021)
Denpasar City is the capital city of Bali Province, with various watersheds that cross Denpasar City. Judging from this, the Denpasar City Government is committed to utilizing the river border into a recreation space as a form of creativity space. By involving the role of the younger generation to use Tukad Bindu as a creative space that changes the face of the river which is seen as slum, a lot of garbage, a place as a washing location for the local community, and has the creepy impression of